A new fatigue protocol to assess postural sway in collegiate female athletes. Issue 4 (2nd October 2019) - Seidi, Foad; Hamedani, Pegah D.; Rajabi, Reza; Sheikhhoseini, Rahman; Khoshroo, Fatemeh
ABSTRACT: Background : Core stability, i.e. the ability to control the position and motion of the body's core has been proposed to be an important factor involved in postural sway. Muscle fatigue may adversely affect the function of core muscles. Although many studies have investigated effects of core muscle fatigue on balance, mostly non-standard fatigue protocols have been used which can potentially call into question the validity of their results. Purpose : This paper contributes to the existing literature by developing a standard functional core fatigue protocol (FCFP) to functionally induce fatigue in all core muscles, and to examine its effects on postural sway in collegiate female athletes. Method : The endurance of core muscles and postural sway was assessed in sixty female collegiate athletes using the Pressure Biofeedback Unit (PBU) and the Force Distribution Measurement-Small multifunction force-measuring plate, respectively. The confidence interval was set at 95% ( p < 0.05). Results : A significant decrease in endurance of core muscles was found in the experimental group after their participation in the FCFP ( p < 0.001). Also, the displacement of the centre of pressure in both 'path length' and 'area' as indices of postural sway significantly increased compared to the related pre-fatigue values ( p < 0.001). Conclusion : The designed FCFP can induce fatigue in core muscles efficiently and has significant negative effects on postural sway in collegiate female athletes.